Branding: Membuat Desain Kemasan Produk Nasi Kebuli Pondok Pesantren Ar-Riyadh Pasuruan dengan Metode Participatory Rural Appraisal: Branding: Creating Packaging Design for Rice Kebuli Products at Ar-Riyadh Islamic Boarding School Pasuruan with the Participatory Rural Appraisal Method - Agustina, Rini; Andayani, Endah; Nurfaizana, Della Rulita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The culinary division 'Riyadh' has been operating since 2003 and is run directly by the students as part of the Santripreneurship activities in the Islamic boarding school environment. Currently, the culinary business ``Riyadh'' is still order-based and has not fully developed into a very productive business group. This culinary division functions as a place for students to learn business and its profits are used to support the needs of the Islamic boarding school. With increasing consumer demand, there is an urgent need to develop this company into a very productive business group. So far, Riyadh's delicious food has only been sold and served in large